Mobile Usage at the Base of the Pyramid in South Africa - World Bank (Washington, DC, 2014)
Mobile phones are the primary means of accessing information or communicating for those who live at the base of the pyramid (BoP). It is likely that the mobile phone will therefore also be the preferred medium to provide value-added services to those at the BoP, whether they are private users or informal businesses, for the foreseeable future. Although the prepaid mobile model has brought voice and text services to this group, sustainable, replicable models for enhanced services, products and applications are far more limited. The purpose of the study is to investigate the demand for mobile applications, services and products, with a view to increasing economic opportunities and improving well-being for users at the BoP. The key objectives of the study are the following: i) to increase understanding of the actual usage of mobile services, products and applications at the BoP, and to understand their potential for economic and social empowerment; ii) to identify scalable examples of services, products and applications at the concept, prototype, or early product-development stages; iii) to develop tools and instruments to map viable operation models and objects of various segments of the BoP markets and to identify user needs; and iv) to formulate recommendations for business planning and policy development that can support this potential.